Oxidative stress markers and brainstem auditory evoked potential in premenopausal, perimenopausal and postmenopausal females - Ashraf, Asma; Naeem, Seher; Akram, Madiha; Saeed, Muniza (Journal of the Pakistan Medical Association, 2025)
Objective: To measure biomarkers of oxidative stress and to determine hearing sensitivity by auditory brainstem response in premenopausal, perimenopausal and postmenopausal women. Method: The cross-sectional, comparative study was conducted in the departments of Physiology and Audiology at the Post-Graduate Medical Institute, Lahore, and the Lahore General Hospital, Lahore, Pakistan, from November 2020 to November 2021, and comprised healthy female subjects grouped into premenopausal group 1, perimenopausal group 2 and postmenopausal group 3 as per their menstrual history. Blood samples were taken for measuring biological indicators of oxidative damage, while auditory integrity was assessed by measuring absolute latencies of waves I, III, V and interpeak latency of waves III and V at an intensity of 80dB by performing brainstem auditory evoked potential. Data was analysed using SPSS 23. Results: Of the 45 subjects, 15(33.3%) with mean age 41.3±1.9 were in group 1, 15(33.3%) with mean age 46.7 ± 3.7 years were in group 2, and 15(33.3%) with mean age 55.8±2.7 years were in group 3. Significantly increased levels of thiobarbituric acid reactive substance were found in group 3 compared to groups 1 and 2 (p<0.05). Regarding auditory brainstem response, a significant increase was observed in absolute latencies of waves I, III, V and interpeak latency between waves III and V in group 3 compared to the other groups (p<0.05). Conclusion: Oxidative stress had a debilitating impact on hearing sensitivity related to the menopausal status of women. Key Words: Menopause, Oxidative stress, Brainstem auditory evoked potential.